Late Presentation of a Congenital Intrinsic Duodenal Obstruction in a Patient with Anorectal Malformation - Mandhan, Parkash; Rathod, Kirtikumar J.; Sankhla, Dilip (Scientific Research, 2013)
Anorectal Malformations are known to be associated with various other congenital anomalies including duodenal atresia. An association of congenital intrinsic duodenal obstruction causing partial duodenal obstruction in a patient with anorectal malformation is not described in literature. We describe a case of delayed presentation of congenital intrinsic duodenal obstruction in a child with high-type anorectal malformations causing diagnostic dilemma.
Keywords: Anorectal Malformations; Duodenal Obstruction; VACTERL Association; Delayed Presentation; Infant